The practice of evangelism - Green, Bryan; Moorhouse lectures (London, UK Hodder and Stoughton, 1951)
Includes bibliographical references.
The Moorhouse lectures for 1951 delived in St Paul's Cathedral, Melbourne.
Keywords: Evangelism